2014
DOI: 10.3389/fmicb.2014.00269
|View full text |Cite
|
Sign up to set email alerts
|

Potential of essential oils for protection of grains contaminated by aflatoxin produced by Aspergillus flavus

Abstract: Aflatoxin B1 (AFB1) is a highly toxic and carcinogenic metabolite produced by Aspergillus species on food and agricultural commodities. Inhibitory effects of essential oils of Ageratum conyzoides (mentrasto) and Origanum vulgare (oregano) on the mycelial growth and aflatoxin B1 production by Aspergillus flavus have been studied previously in culture medium. The aim of this study was to evaluate aflatoxin B1 production by Aspergillus flavus in real food systems (corn and soybean) treated with Ageratum conyzoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
(29 reference statements)
2
23
1
Order By: Relevance
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in recent years have focused on the antifungal potential of EOs against Aspergillus and Fusarium genera, mainly on cereal matrices such as rice, oat, maize or wheat (Fandohan et al 2004; Marin et al 2004; Velluti et al 2004; Sumalan et al 2013; Esper et al 2014; Prakash et al 2015; Kumar et al 2016; Santamarina et al 2016; Tagne et al 2016; Tian et al 2016; Boukaew et al 2017; Bozik et al 2017). However, the available literature provides limited data concerning comprehensive studies on the effect of EOs on the inhibition of both Fusarium growth and mycotoxin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of researches have focused on evaluation of inhibitory effect of EOs against A. flavus growth and AFB1 production. For example, the mycelial growth of A. flavus and production of AFB1 effectively inhibited by adding oregano oil in corn and soybean seeds (Esper, Gonçalez, Marques, Felicio, & Felicio, 2014). Recent studies have also demonstrated that EOs (e.g., oregano, thyme, clove, and cinnamon oil) can be effective for controlling fusarium mycotoxins in maize and wheat grains (Magan, Aldred, Mylona, & Lambert, 2010; Velluti et al., 2004).…”
Section: Mycotoxin Management In Cereal‐based Foodmentioning
confidence: 99%